2015
DOI: 10.3390/ijerph13010064
|View full text |Cite
|
Sign up to set email alerts
|

Study on Oxygen Supply Standard for Physical Health of Construction Personnel of High-Altitude Tunnels

Abstract: The low atmospheric pressure and low oxygen content in high-altitude environment have great impacts on the functions of human body. Especially for the personnel engaged in complicated physical labor such as tunnel construction, high altitude can cause a series of adverse physiological reactions, which may result in multiple high-altitude diseases and even death in severe cases. Artificial oxygen supply is required to ensure health and safety of construction personnel in hypoxic environments. However, there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…For Node 1, in the ventilation network, when the air density changes little, the air quantity flowing in Node i is equal to that flowing out of Node i, i.e., the algebraic sum at any node is zero, as shown in Equations (10) and (11).…”
Section: Calculation Methods Of the Natural Wind Velocity In The Tunnementioning
confidence: 99%
See 1 more Smart Citation
“…For Node 1, in the ventilation network, when the air density changes little, the air quantity flowing in Node i is equal to that flowing out of Node i, i.e., the algebraic sum at any node is zero, as shown in Equations (10) and (11).…”
Section: Calculation Methods Of the Natural Wind Velocity In The Tunnementioning
confidence: 99%
“…Good ventilation results are obtained in extra-long tunnels after applying this ventilation mode, but the drawback is high construction costs due to large occupied space in the tunnel [10]. Shafts or inclined shafts serve as air inlets or outlets in segmented longitudinal ventilation, the extra-long tunnel is divided into several segments [11]. Construction expense will obviously decline compared to semi-transverse ventilation [12].…”
Section: Introductionmentioning
confidence: 99%
“…These electrical signals are a combination of brain rhythms at different frequency levels falling into differing frequency, including delta waves (<4 Hz), theta waves (4-7 Hz), alpha waves (7)(8)(9)(10)(11)(12), beta waves (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma waves [5]. Studies have shown that delta activities are high during sleep while theta index activities are high on the early phase of sleepiness [6].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the pressure of atmospheric significantly affects the functions of the human body because low atmospheric pressure leads to a decrease in partial oxygen pressure [26]. Thus, the change in atmospheric pressure and the molecular pressure of oxygen are essential variables affecting oxygen transport and human respiration in altitude [27]. Many studies have shown that the maximal workload, as well as the uptake of oxygen, decreases as the atmospheric pressure and the partial pressure of oxygen decreases (in another word as altitude increases) [28,29]".…”
Section: Introductionmentioning
confidence: 99%
“…The physical workload of male workers in the construction industry in Norway is investigated by Lunde and his colleagues who describe the cardiovascular burden of 255 such workers [7]. Construction workers in Chinese high altitude tunnels face a different set of risks and Guo and colleagues looked at the oxygen supply standards which might apply when workers are engaged in heavy physical work in tunnels [8]. Importantly the authors moot a standard for oxygen supply to this workforce.…”
mentioning
confidence: 99%